Could METS-VF provide a clue as to the formation of kidney stones? - Guo, Zhenyu; Li, Guoxiang; Chen, Yan; Fan, Shuai; Sun, Shuai; Hao, Yunwu; Wang, Wei (Frontiers in Endocrinology, 2023)
Objective The lifetime occurrence rate of kidney stones is 14%, making it one of the most prevalent urological conditions. Other contributing elements, such as obesity, diabetes, diet, and heredity, are also taken into account. Our research sought to explore the potential link between high visceral fat scores (METS-VF) and the occurrence of kidney stones, as a means of understanding how to prevent them. Methods This research utilized data from the National Health and Nutrition Examination Survey (NHANES), mirroring the demographics of the United States. We carried out an in-depth analysis of the connection between METS-VF and kidney stones, based on data from 29,246 participants in the National Health and Nutrition Examination Survey spanning 2007 to 2018, involving logistic regression, segmentation, and dose-response curve analysis. Results Our study of 29,246 potential participants found that METS-VF was positively associated with the prevalence and progression of kidney stones. After subgroup analysis by gender, race, blood pressure, and blood glucose, our results showed that the ORs for METS-VF and kidney stones were (1.49, 1.44) in males and females, respectively; while in Mexicans, whites, blacks, and In other populations, the OR values were (1.33, 1.43, 1.54, 1.86); in hypertensive and normal populations, the OR values were (1.23, 1.48); in diabetic patients and normoglycemic patients were (1.36,1.43). This proves that it works for all groups of people. Summary Our studies demonstrate a strong connection between METS-FV and the emergence of kidney stones. It would be beneficial to investigate METS-VF as a marker for kidney stone development and progression in light of these findings.